Homem do Barranco : pesquisa e dramaturgia na cena ribeirinha - Ferreira, Carlos Roberto (2014)
Rewrite the dramatic poem man Barranco, Carlos Roberto Ferreira, whose image process and site investigation found support in the community of São Gonçalo Beira Rio Cuiaba, Mato Grosso. The rewriting is supported by a look at the neighborhood in this time, with records of changes in the last two decades and studies of contemporary theater in it. Research and drama performed for the first scenario are printed on the result of the experience of living with the village - crafted from clay, of belonging and collective memory. The text rewritten Arrimo Waters's proposal is staging a performance, revealing it simultaneously to the present time, plagued as breadwinner, flow and counter-flow changes of sociocultural and environmental image of São Gonçalo Riverside neighborhood today.